Prace konserwatorskie i badania architektoniczne klauzury dawnego opactwa cysterskiego w Krzeszowie po drugiej wojnie światowej - Łużyniecka, Ewa; Dąbkowska, Monika (Saeculum Christianum. Pismo Historyczne, 2019)
This article is about conservational and study works on the enclosure of an old cystercian abbey in Krzeszów, that were made after the Second World War. Post-war history of conservation of this monument exhibits two periods. The first one covers 50 post-war years, where only routine maintenance was done. The latter period began at the beginning of the XXI century. Since then fragments of the building were renovated piece by piece. Current cultural and touristic needs were taken into consideration.Revalorization of Krzeszów Abbey in years 2007-2008 and since 2014 revealed the basements and relicts of the groundfloor of the south and west wings of the complex. At the same time the architectural studies were made, resulting in new conclusions of transformations of this building.